What is in It for Them? Understanding the Impact of a ‘Support, Appreciate, Listen Team’ (SALT)-Based Suicide Prevention Peer Education Program on Peer Educators - Zachariah, Bobby; de Wit, Emma E.; Bahirat, Jyotsna Dnyaneshwar; Bunders-Aelen, Joske F. G.; Regeer, Barbara J. (School mental health, 2018)
Youth suicide is a public health problem in India, and young people in school, particularly adolescents, experience heavy psychological burden. Prevention programs, involving peer educators (PEs), have proved useful strategies to address this problem, but their impact on the PEs is less understood, particularly in India. This qualitative study aims to explore the changes observed in PE students who were involved in a ‘mindfulness’ and ‘Support-Appreciate-Listen–Team’ (SALT)-based peer education program to address suicidal behavior in Indian school students. One hundred and fourteen students were trained as PEs in six high schools in Pune to identify and respond to the needs of students in distress. By listening to the narratives of the PEs, their parents, school authorities, and the associated NGO team, we reflect on perceived social, emotional, behavioral, and cognitive changes in PEs. The PEs demonstrated enhanced caring for those in distress both inside and outside school by improved listening skills, self-awareness, care, and empathy. Furthermore, the program had a positive impact on their broad emotional intelligence and PEs expressed increased ownership of life, taking action, and seeking support where needed. The study concludes that mindfulness and SALT-based peer education (PE) programs are valuable for the PEs. This could be used to motivate PEs to volunteer in such programs. Other results are discussed and further research areas are suggested.